2012
DOI: 10.1097/ta.0b013e31825ac511
|View full text |Cite
|
Sign up to set email alerts
|

Does needle thoracostomy provide adequate and effective decompression of tension pneumothorax?

Abstract: Thoracic insufflation produced a reliable and easily controlled model of tPTX. NT was associated with high failure rates for relief of tension physiology and for treatment of tPTX-induced PEA and was due to both mechanical failure and inadequate tPTX evacuation. This performance data should be considered in future NT guideline development and equipment design.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
41
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(44 citation statements)
references
References 23 publications
0
41
0
3
Order By: Relevance
“…However, depending on the needle or cannula used, this is often ineffective at relieving the tension, as the needle may not be long enough to reach the pleural space, and it may dislodge or kink, rendering it useless, potentially allowing the tension pneumothorax to recur. 16,17 Thoracostomy is therefore recommended over needle decompression. [18][19][20] Thoracostomy is achieved by making a skin incision followed by blunt dissection with forceps or finger through the intercostal muscles and pleura in the same location that an intercostal drain is usually placed (fourth or fifth intercostal space, in the mid-axillary line).…”
Section: Management Of Reversible Causesmentioning
confidence: 99%
“…However, depending on the needle or cannula used, this is often ineffective at relieving the tension, as the needle may not be long enough to reach the pleural space, and it may dislodge or kink, rendering it useless, potentially allowing the tension pneumothorax to recur. 16,17 Thoracostomy is therefore recommended over needle decompression. [18][19][20] Thoracostomy is achieved by making a skin incision followed by blunt dissection with forceps or finger through the intercostal muscles and pleura in the same location that an intercostal drain is usually placed (fourth or fifth intercostal space, in the mid-axillary line).…”
Section: Management Of Reversible Causesmentioning
confidence: 99%
“…Cadaver [47], animal [48][49][50], and clinical [51][52][53][54] studies have suggested that use of a small (3.2 cm) needle in the standard site (second intercostal space, midclavicular line) is not reliable, likely due to the thickness of the chest wall at this site and the small size of the needle or catheter. Even when proper placement is confirmed laparoscopically in animal models, Martin and colleagues showed that a 14-gauge angiocatheter fails to relieve tension physiology 64 % of the time [48]. The fourth or fifth intercostal space at the anterior axillary line is consistently thinner than the traditional site in multiple radiographic studies [52][53][54], which suggests that it may be a superior site for needle thoracostomy.…”
Section: Tension Pneumothoraxmentioning
confidence: 99%
“…Advanced Trauma Life Support (ninth edition) guideline suggests, "inserting a large-caliber needle into the second ICS in the MCL of the affected hemithorax" for the emergency management of tension pneumothorax [3]. Needle thoracostomy success rates vary by location, and its use has also been questioned in the literature [4][5][6]. Various needle lengths and locations were proposed and fifth intercostal space (ICS) emerged as the most popular alternative.…”
Section: Introductionmentioning
confidence: 99%